Investment and Income Effects of Land Regularization : The Case of Nicaragua - Deininger, Klaus; Chamorro, Juan Sebastian (World Bank, Washington, DC, 2013)
The authors use data from Nicaragua to examine the impact of the award of registered and nonregistered title on land values and on investments attached to land. They find that receipt of registered title increases land values by 30 percent and greatly increases the propensity to invest, bringing investment closer to the optimum. Consistent with descriptive statistics indicating great demand for regularization of land rights, especially from the poor, this finding suggests that titling can have a positive distributional effect. Of overriding importance, however, are the legal validity and official recognition of the titles issued.